Hyoid bone impingement contributing to symptomatic atherosclerosis of the carotid bifurcation - Shirley Liu, MD; Nariman Nezami, MD; Alan Dardik, MD, PhD; Naiem Nassiri, MD (Journal of Vascular Surgery Cases and Innovative Techniques, 2020)
Symptomatic carotid artery disease caused by hyoid bone compression is rare, although scant reports describe cerebrovascular events due to this mechanical interference leading to entrapment, embolism, dissection, atherosclerotic stenosis, and pseudoaneurysm formation. This report describes a patient presenting with left-sided paresis and paresthesia who was found to have focal right carotid stenosis secondary to impingement of the carotid bulb by an elongated hyoid bone. Whereas previous cases describe hyoid bone resection, we describe successful management with endarterectomy and carotid mobilization without hyoid resection, with long-term follow-up demonstrating a widely patent carotid system without recurrent impingement. Keywords: Hyoid bone, Carotid artery, Carotid stenosis, Atherosclerosis, Cerebral infarction